Pengaruh Maintenance pada Rampdoor untuk Kelancaran Proses Bongkar Muat di Kapal RO-RO KM Mutiara Ferindo V - Firmansyah Pratama Yudha; Kuncowati Kuncowati; Elva Febriana Anggraeny (Indonesian Maritime Researchers and Lecturers, 2026)
The existence of the ramp door plays a vital role as the main pathway for vehicle loading and unloading activities on the Ro-Ro ship KM Mutiara Ferindo V, especially amidst high sailing intensity. Therefore, this research was conducted with the aim of evaluating the extent to which ramp door maintenance is implemented and its impact on the smoothness of the loading and unloading process. Using a Mixed Methods approach with a Sequential Explanatory design, this research collected quantitative data from 26 respondents (saturated sampling) through questionnaires, which were then tested using simple linear regression and a t test. Meanwhile, qualitative data were explored through observations and in-depth interviews with the Chief Officer and Bosun, and then analyzed using the Miles and Huberman interactive model. Statistical findings confirmed that maintenance has a positive and significant impact on loading and unloading efficiency, evidenced by the t-count value (3.217) which exceeded the t table (2.064) at a significance level of 0.004 (< 0.05). However, the qualitative review revealed that the realization of maintenance in the field has not been optimal due to the limited ship berthing time (turnaround time). This condition creates two main obstacles: the disruption of the ramp door's mechanical movement and a decrease in the speed of vehicle circulation due to drivers' safety concerns. In conclusion, strict compliance with the Planned Maintenance System (PMS) is an absolute prerequisite to realize safe, smooth, and efficient loading and unloading operations.